2017
DOI: 10.1080/09712119.2017.1386108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbiotic FS supplementation on growth performance, nutrient digestibility, blood profiles, and faecal scores in weanling pigs

Abstract: This study was conducted to investigate the effects of Herbiotic FS supplementation on growth performance, nutrient digestibility, blood characteristics, and faecal scores in weanling pigs. A total of 150 weanling pigs [(Landrace×Yorkshire)×Duroc] with an average initial body weight of 8.02 ± 0.92 kg were randomly assigned to 5 dietary treatments (5 replicate pens per treatment with 6 pigs per pen). The dietary treatments were as follows: (1) negative control: basal diet, (2) positive control: basal diet + 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The study by Lei et al. ( 2018 ) was conducted to investigate the effects of dietary supplementation with a phytogenic feed additive and a positive control containing apramycin (150 mg/kg feed) on growth performance, nutrient digestibility, blood characteristics and faecal scores in weaned pigs. A total of 150 pigs ((Landrace × Yorkshire) × Duroc; BW 8.0 kg) were randomly assigned to treatments with five pens per treatment each including six pigs.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Lei et al. ( 2018 ) was conducted to investigate the effects of dietary supplementation with a phytogenic feed additive and a positive control containing apramycin (150 mg/kg feed) on growth performance, nutrient digestibility, blood characteristics and faecal scores in weaned pigs. A total of 150 pigs ((Landrace × Yorkshire) × Duroc; BW 8.0 kg) were randomly assigned to treatments with five pens per treatment each including six pigs.…”
Section: Assessmentmentioning
confidence: 99%
“…( 2012 ) and Zhao and Kim ( 2015 ), 100 mg/kg feed; Lei et al. ( 2018 ), 150 mg/kg feed; Zhang and Kim ( 2014 ) and Hossain et al. ( 2016 ), 165 mg/kg feed; Yoon et al.…”
Section: Assessmentmentioning
confidence: 99%
“…Herbs and essential oils are used in pig nutrition due to their antibacterial, anti-inflammatory, antioxidant and anti-parasite properties Grela and Klebaniuk, 2007;Liu et al, 2017;Lei et al, 2018;Zhao et al, 2019). The characteristics of selected herbs used in pig nutrition are presented in Table 1.…”
Section: Herbs and Herbal Extracts (Phytobi-otics)mentioning
confidence: 99%
“…Liu et al (2017) found that a mix of herbal extracts (Scutellaria baicalensis and Lonicera japonica) used as an addition to the diets of sows under thermal stress improves the intake and digestibility of feed and has a beneficial effect on the weight gain and weaning weight of piglets. Herbal mixes are widely used as additives to feed for piglets and weaners (Khan et al, 2009;Hanczakowska and Świątkiewicz, 2012;Lei et al, 2018;Zhao et al, 2019;Wang et al, 2020). Hanczakowska and Świątkiewicz (2012) demonstrated that an extract from sage, lemon balm, nettle and echinacea added in the amount of 500 mg/kg feed for piglets contributed to extending their intestinal villi, and thus improved the digestibility and conversion of the feed ration.…”
Section: Herbs and Herbal Extracts (Phytobi-otics)mentioning
confidence: 99%
“…In the context of the gradually restricted or fully banned use of antibiotics in the diets of food-producing animals, phytogenic feed additives like medicinal plants and their extracts have attracted wide spread attention due to their plant-derived property and growthpromoting effect (Lei, Yun, Kang, & Kim, 2018;Mendel, Chłopecka, Dziekan, & Karlik, 2017;Si et al, 2006). Numerous previous studies have shown that plant extract scan be effective in improving the growth and health of pigs (Windisch, Schedle, Plitzner, & Kroismayr, 2008).…”
Section: Effects Of Plant Extractmentioning
confidence: 99%